ENDOSCOPE (2007)
An endoscope includes an electronic endoscope unit and an external control unit for transmitting and receiving a signal to and from the electronic endoscope unit . The electronic endoscope unit includes a front end section having an imaging element and a cable housing a wire for connecting the front end section to the external control unit . The front end section includes a CDS circuit for performing a correlated-double sampling process for an analog signal output from the imaging element and an A/D converter for converting the analog signal subject to the correlated-double sampling process into a digital signal.